Does she compensate the victim while he punishes the perpetrator? No gender differences in anonymous economic games across 11 nations - Angela R. Dorrough; Maria I.T. Olsson; Laura Froehlich; Andreas Glöckner; Sarah E. Martiny (Journal of Behavioral Decision Making, 2021)
Social role theory posits that occupational gender roles give rise to gender differences in behavior, such that men and women engage in qualitatively different prosocial behaviors. Therefore, we expected that women who observed an unfair situation (involving a victim and a perpetrator) would respond by demonstrating communal prosocial behavior (by compensating the victim), whereas men would respond with agentic prosocial behavior (by punishing the perpetrator). Furthermore, on the basis of social role theory, we expected that gender differences would be more pronounced in countries with a more unequal distribution of men and women in communal and agentic occupational roles. The current research tested the predictions using an economic game. Two studies consisting of samples from 10 countries (Study 1, N = 1,791) and a student sample from Germany (Study 2, N = 193) showed no support for the predicted gender differences in prosocial behavior and no systematic relationship between prosocial behavior and gender roles across countries.
Keywords: 650; agentic; communal; gender differences; helping; prosocial behavior; social role theory